Cognitive pathways to depression and suicidality: the role of reflective rumination and modes of processing - Brennan, K (2011)
Ruminative thinking – repetitively fixating on symptoms of distress and the causes and consequences of these symptoms – is strongly implicated in the onset, persistence and severity of depressive symptoms (Just and Alloy, 1997; Nolen-Hoeksema and Morrow, 1991). However other, less evaluative, forms of self-focused thinking that involve active problem-solving aimed at understanding or overcoming one’s problems are generally considered less maladaptive. Consistent with this, research has indicated that the reflective pondering subscale of the Response Style Scale is associated with adaptive forms of coping, is unrelated to cognitive biases, and is less consistently associated with concurrent and longitudinal depressive symptoms when compared with other forms of rumination (Burwell and Shirk, 2007; Joorman et al., 2006; Treynor et al., 2003). Recent studies however have indicated an association between reflection and suicidal ideation, calling into question the suggestion that reflection is a constructive response style, at least in the case of suicidality (Miranda and Nolen-Hoeksema, 2007; Surrence et al., 2009). Indeed little attention has been directed to the question of the psychological conditions under which reflection may be an adaptive or maladaptive process, although the literature suggests there is need for such an examination. The first aim of this thesis was to investigate the associations between suicidal thoughts and subtypes of rumination among individuals with a history of recurrent suicidal depression. The results of this investigation identify a concurrent relationship between higher levels of reflection and increased suicidal cognitions and highlight the distinct quality of this relationship which, unlike brooding, is independent of depressive symptoms. Motivated by the contradictory or discrepant findings related to reflection in the literature, the second aim of this thesis was to investigate the implications of more recent theories of self-focused attention and modes of processing (Watkins and Teasdale, 2004; Segal et al., 2002) for the conditions in which reflection is, or is not, adaptive. Levels of mindfulness and memory specificity were investigated as potential moderators of the relationship between reflective thinking and depressive symptoms. The results indicate that, for those participants low in both mindfulness and memory specificity, higher levels of reflection are related to more depressive symptoms. This suggests perhaps that, unlike other forms of rumination which are inherently negative, reflection may represent a response to depressed mood that is susceptible to the effect of individual state or trait processing. The cognitive problem-solving aspect of reflection may be hampered under conditions of unspecific, abstract processing and a mind tending toward self-judgment and reactivity. In conclusion, the results of this study suggest that reflection cannot be assumed to be a benign or helpful process – particularly in the context of suicidal depression and among individuals with certain cognitive profiles.